A self-repairing modified lignin-based polyester polyol coating material and preparation method thereof
By using self-repaired modified lignin-based polyester polyol coating materials in bio-based controlled release fertilizers, combined with nano-toughening agents and polyurea, a dynamic covalent bond network is formed, which solves the problem of poor membrane shell toughness and achieves a longer controlled release period and self-healing ability.
Patent Information
- Application Number
- CN202410370450.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-29
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-03-29
AI Technical Summary
The existing bio-based controlled release fertilizer membrane shell has poor toughness and is prone to damage during production and transportation, resulting in too fast nutrient release and affecting the quality of controlled release.
The self-repaired modified lignin-based polyester polyol coating material is used to construct a reversible covalent bond network on the surface of the fertilizer, which increases the toughness and self-healing ability of the membrane material, and introduces nano-toughening agents and polyurea to form a dynamic covalent bond network.
The toughness and controlled release period of fertilizer membrane shell are improved, the problem of membrane shell damage during production is reduced, and the rapid self-repair of membrane shell is achieved under visible light.
Smart Images

Figure CN118271131B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field, and in particular to a self-repairing modified lignin-based polyester polyol coating material and a preparation method thereof. Background Art
[0002] my country is a large agricultural country, and chemical fertilizers have made an indelible contribution to my country's grain output. However, traditional chemical fertilizers usually have problems such as low nutrient utilization rate, time-consuming and labor-intensive application, and environmental pollution caused by excessive application. With the development of science and technology, slow-release fertilizers have gradually replaced traditional chemical fertilizers. At present, the common controlled-release fertilizers on the market are mainly divided into petrochemical-based coated controlled-release fertilizers and bio-based coated controlled-release fertilizers. Petrochemical-based coating materials are expensive, not environmentally friendly, and non-renewable, while bio-based coating materials are green, environmentally friendly, low-cost, and renewable. Therefore, bio-based coated controlled-release fertilizers are a major trend in the future. However, bio-based coated controlled-release fertilizers have the disadvantages of short nutrient controlled-release cycle and poor controlled-release quality of film materials. On the one hand, the coated fertilizers synthesized using bio-based film materials contain many pores or a large number of hydrophilic groups such as hydroxyl groups, which accelerate the entry of water into the film material, causing the film material to absorb water and swell, and have strong permeability, thereby accelerating the release of nutrients, greatly shortening the controlled-release period of nutrients, and affecting its controlled-release quality. On the other hand, most bio-based membrane materials have a highly cross-linked network structure with poor toughness. The collision and friction between fertilizer particles during the production process can easily cause the membrane shell to tear or break, causing the fertilizer particles to absorb water and release nutrients prematurely and fail to achieve the corresponding controlled release period.
[0003] Lignin is a network structure polymer formed by phenylpropane monomers connected by carbon-carbon bonds and ether bonds. The global annual output is about 50 million tons, which is the second most abundant biomass material. Therefore, lignin has extremely high utilization value and development prospects. However, due to the large number of impurities in lignin polyols, many small-molecule alcohols will form an implosion phenomenon during the reaction with isocyanate. During the coating process, lignin-based polyols react violently with isocyanate and solidify quickly. When the two are mixed and added to the coating pot, the coating liquid has not yet been evenly coated on the surface of the fertilizer particles. It has solidified. Many fertilizer particles will all stick together due to the uneven coating liquid. As the coating liquid on the surface of the fertilizer particles solidifies, the fertilizer particles will tear apart, resulting in the tearing of the membrane shell on the surface of the fertilizer particles, and the rapid release of nutrients. In addition, since lignin is rich in hydroxyl groups and has strong hydrophilicity, it accelerates the release of nutrients and affects the controlled release quality. At present, most of the modification of lignin is to make it hydrophobic. However, the existing modification methods are difficult to solve the problem of damage of lignin-based coating materials during production or nutrient release. Summary of the invention
[0004] In view of the above-mentioned prior art, the purpose of the present invention is to provide a self-healing modified lignin-based polyester polyol coating material and a preparation method thereof. The self-healing temperature range of the present invention is 0-80°C. By constructing a reversible covalent bond network on the fertilizer surface, it solves the problems of friction and tearing between the fertilizer membrane shell and the equipment in production, friction and tearing between the fertilizer membrane shells, and membrane shell damage during fertilizer transportation; lignin and nano-toughening agents are cross-linked into a dynamic covalent bond network to increase the toughness and other mechanical properties of the membrane material, providing a good foundation for creating a more environmentally friendly controlled-release fertilizer. The coating has good mechanical properties, and while having self-healing capabilities, it can effectively protect the internal fertilizer particles.
[0005] To achieve the above object, the present invention adopts the following technical solution:
[0006] The first aspect of the present invention provides a self-repairing modified lignin-based polyester polyol coating material, comprising the following raw materials in parts by weight:
[0007] 50-100 parts of lignin-based polyester polyol, 0-2 parts of accelerator and 1-20 parts of self-healing adhesive;
[0008] The self-healing adhesive is obtained by reacting a first component and a second component, wherein the first component is one or more of adenosine-2', 3'-o-phenyl borate, bis(4-aminophenyl) diselenide, and di-(1-hydroxyethyl) ditelluride; and the second component is one or more of 2-benzyl isocyanate, 2-methoxyphenyl isocyanate, and 4-methoxyphenylethyl isocyanate.
[0009] Preferably, the self-repairing modified lignin-based polyester polyol coating material comprises the following raw materials in parts by weight:
[0010] 50-100 parts of lignin-based polyester polyol, 1.5-2 parts of accelerator and 1-20 parts of self-healing adhesive.
[0011] Preferably, the accelerator is 5-aminolevulinic acid hydrochloride.
[0012] Preferably, the reaction conditions of the self-healing adhesive are:
[0013] The first component and the second component are mixed in a mass ratio of (4-6): (2-4), reacted at 20-30°C for 1-2 hours, dried at 65°C for 10-14 hours, and bubbles were removed to obtain a self-healing adhesive.
[0014] Preferably, the lignin-based polyester polyol is prepared by the following method:
[0015] Lignin polyol and amino-containing dicarboxylic acid are mixed in a molar ratio of 1:1 to obtain a mixed solution, and then a nano-toughener is added to the mixed solution in an amount of 1‰ by mass of the mixed solution. The mixture is reacted at 160°C-230°C for 6-10 hours. After the reaction, the product is dehydrated to obtain a lignin-based polyester polyol.
[0016] Preferably, the amino-containing dicarboxylic acid is one or more of glutamic acid, cysteine and aspartic acid.
[0017] Preferably, the nano toughening agent is prepared by the following method:
[0018] Concentrated sulfuric acid and tetrabutyl titanate are mixed to obtain a mixed solution, and then nano-silicon dioxide is added to the mixed solution, and the mixture is vibrated for 2 hours. The precipitate is collected by centrifugation and dried to obtain a nano-toughening agent.
[0019] Preferably, the ratio of the added amounts of concentrated sulfuric acid, tetrabutyl titanate and nano-silicon dioxide is (2-4) ml: (25-35) ml: (0.1-1) g.
[0020] Preferably, the lignin polyol is prepared by the following method:
[0021] Lignin, glycerol, polyethylene glycol and lactic acid are mixed to obtain a mixture, and the mixture is reacted at 140-180° C. for 0.5-1.5 hours to obtain lignin polyol.
[0022] Preferably, the mass ratio of lignin, glycerol, polyethylene glycol and lactic acid is (25-35):(35-45):(150-170):(10-14).
[0023] The second aspect of the present invention provides a method for preparing the above-mentioned self-repairing modified lignin-based polyester polyol coating material, comprising the following steps:
[0024] The lignin-based polyester polyol, the accelerator and the self-healing adhesive are mixed evenly, stirred continuously for 10-20 minutes under a nitrogen atmosphere, bubbles are removed, and the mixture is allowed to stand for 2-4 hours to obtain a self-healing modified lignin-based polyester polyol coating material.
[0025] The third aspect of the present invention provides the use of the self-repairing modified lignin-based polyester polyol coating material in the preparation of controlled-release fertilizers.
[0026] The fourth aspect of the present invention provides a coated controlled-release fertilizer, comprising a fertilizer core and the above-mentioned self-healing modified lignin-based polyester polyol coating material sprayed on the surface of the fertilizer core; the mass of the self-healing modified lignin-based polyester polyol coating material is 4-6% of the mass of the fertilizer core.
[0027] A fifth aspect of the present invention provides a method for preparing the above-mentioned coated controlled-release fertilizer, comprising the following steps:
[0028] The self-repairing modified lignin-based polyester polyol coating material is uniformly sprayed on the surface of the fertilizer core at a rotation speed of 20-23 rps at a pressure of 0.2-0.5 MPa, and cured at 50-70° C. for 10-15 minutes to obtain a coated controlled-release fertilizer.
[0029] The mechanism of action of the self-repairing modified lignin-based polyester polyol coating material of the present invention is:
[0030] The lignin-based polyester polyol of the present invention is prepared from lignin-based polyol, nano toughening agent and amino-containing dicarboxylic acid. The lignin-based polyol contains many impurities. When the lignin-based polyol reacts with isocyanate to form a polyurethane film, these impurities will exist in the film, resulting in the formed film being very brittle and not dense. The nano toughening agent and amino-containing dicarboxylic acid are added. The nano toughening agent, on the one hand, serves as a catalyst for forming polyester, and on the other hand, can lock part of the impurities in the lignin during film formation, thereby increasing the toughness of the film after film formation. The amino-containing dicarboxylic acid is added to form the polyester polyol, which can reduce the hydroxyl value of the lignin-based polyol, reduce the severity of the film-forming reaction, and avoid the explosion phenomenon. Moreover, when the amino-containing dicarboxylic acid is added to synthesize the polyester polyol, the later high-temperature reaction can remove water and the remaining small molecule alcohols in the lignin-based polyol, thereby making the product purer. The three complement each other and work together, and none of them is indispensable.
[0031] The first component and the second component in the self-healing adhesive are directly mixed and stirred evenly to pre-crosslink the -OH of the covalent bond (borate bond, diselenide bond, ditelluride bond) in the first component with the -NCO of the isocyanate (2-benzyl isocyanate, 2-methoxyphenyl isocyanate, 4-methoxyphenylethyl isocyanate) in the second component, and the reversible covalent bonds are evenly dispersed in the generated viscous prepolymer solution. These reversible covalent bonds (borate bond, diselenide bond, ditelluride bond) have good mobility, so that the film material has a good repair effect after rupture. For example, in the production process of controlled-release fertilizer, after the coating liquid is sprayed onto the surface of the fertilizer particles, when the coating liquid begins to solidify on the surface of the fertilizer particles, the fertilizer particles will keep rolling in the drum. When the coating liquid solidifies, it will cause adhesion and tearing between the fertilizer particles, and the Se-Se bond in the fertilizer membrane shell will be broken. The bond energy of the Se-Se bond is very low, and the broken -Se -Originally, it has high mobility under visible light conditions. After adding the promoter, the photosensitivity and mobility of -Se- are further improved. Therefore, the broken -Se- under visible light will quickly and reversibly combine into new Se-Se bonds, thereby quickly repairing the torn membrane shell; then, lignin-based polyester polyols are added to the generated viscous prepolymer solution, and the -OH in the lignin-based polyester polyols will form polyurethane with -NCO, and the -NH2 in the lignin-based polyester polyols will form polyurea with -NCO. The presence of polyurea can greatly improve the hydrophobicity of the membrane material and increase the controlled release period of the fertilizer; finally, the three components will react to generate a network structure with a high degree of cross-linking and reversible dynamic covalent bonds. When the fertilizer membrane shell is damaged, the presence of the reversible dynamic covalent bonds can enable the membrane shell to be quickly repaired, and the presence of polyurea effectively improves the hydrophobic properties of the membrane material and increases the controlled release period of the fertilizer.
[0032] In addition, the present invention adds self-repairing adhesive and nano-toughening agent to the coating material in an original way, and also introduces polyurea into the coating material, wherein the nano-toughening agent not only improves the toughness and other mechanical properties of the membrane shell, but also improves the compactness of the fertilizer particle membrane shell; the self-repairing adhesive provides a reversible covalent bond (such as borate bond, diselenide bond, ditellurium bond); and the amino-containing dicarboxylic acid provides an amino group, which provides a basis for the subsequent formation of polyurea. In the formation process of the bio-based membrane material, the self-repairing adhesive and the nano-toughening agent have a synergistic effect. The nano-toughening agent is dispersed into the membrane material and can jointly construct a denser network structure with the dynamic covalent bond, so that the controlled release period, self-repairing performance and toughness of the controlled-release fertilizer are greatly improved.
[0033] Beneficial effects of the present invention:
[0034] (1) The present invention solves the problem of poor toughness of the membrane shell of the bio-based controlled-release fertilizer, enhances the various mechanical properties of the membrane shell, and reduces the damage problem of the membrane shell during the production process.
[0035] (2) The present invention synthesizes lignin-based polyester polyols by a simpler synthesis method and introduces a reversible covalent bond network, which is applied to fertilizer film materials to solve the problem of film shell tearing during the production process of fertilizer particles.
[0036] (3) The present invention introduces amino groups into the synthesized lignin polyester polyol, so that when it reacts with isocyanate to form a film material, a mixture of polyurethane and polyurea is formed, thereby greatly improving the hydrophobicity of the fertilizer film material and increasing the controlled release period of the fertilizer. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 :Schematic diagram of the synthesis route of lignin-based polyester polyols;
[0038] Figure 2 : Fourier transform infrared spectrum (FTIR) of film material;
[0039] Figure 3 : Scanning electron microscope (SEM) images of membrane shell cross section and surface;
[0040] Figure 4 : N element release curve;
[0041] Figure 5 : Comparison of self-repair of membrane materials under visible light;
[0042] Figure 6 : Comparison of films with and without nano-toughening agents. DETAILED DESCRIPTION
[0043] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.
[0044] In order to enable those skilled in the art to more clearly understand the technical solution of the present application, the technical solution of the present application will be described in detail below in conjunction with specific embodiments.
[0045] The test materials used in the examples of the present invention are all conventional test materials in the art and can be purchased through commercial channels.
[0046] Among them, lignin, CAS No: 8068-05-1; propylene glycol, CAS No: 56-81-5;
[0047] Lactic acid, CAS No: 50-21-5; Polyethylene glycol 400, CAS No: 25322-68-3;
[0048] Nano-silica was purchased from the official website of MacLean Reagent, CAS number: 60676-86-0, specification: 99.5%, 50 ± 5 nm;
[0049] The promoter used in the examples is 5-aminolevulinic acid hydrochloride, purchased from Shanghai Jizhi Biochemical Technology Co., Ltd., CAS No.: 5451-09-2, purity 96%.
[0050] The di-(1-hydroxyethyl) ditelluride used in the examples was prepared by the following method:
[0051] (1) Add 7.66 g of tellurium, 2.27 g of sodium borohydride and 150 mL of deionized water into a 500 mL round-bottom flask and stir at 40 °C under argon protection for 3 h;
[0052] (2) Cool to room temperature to obtain a transparent purple-red aqueous solution. Add 7.50 g of 2-bromoethanol to 100 mL of deoxygenated THF, stir at 45° C. under argon protection for 5 h, extract with dichloromethane, dry over anhydrous MgSO4, concentrate the filtrate under reduced pressure, and purify the residue by silica gel column chromatography (ethyl acetate: dichloromethane = 1:1 v / v) to obtain di-(1-hydroxyethyl) ditelluride, i.e. ((HOC2H4Te)2).
[0053] Example 1: Preparation of self-repairing modified lignin-based polyester polyol coating material
[0054] (1) 3 ml of concentrated sulfuric acid and 30 ml of tetrabutyl titanate were added to a 50 ml glass centrifuge tube, and then 0.5 g of nano-silica was added to the glass centrifuge tube, and the mixture was placed under continuous ultrasonic vibration for 2 hours to obtain a mixture; the mixture was then centrifuged in a high-speed centrifuge for 5 minutes (10,000 rpm), and the nano-silica loaded with tetrabutyl titanate and concentrated sulfuric acid was collected after removing the supernatant, and dried in a vacuum drying oven overnight and collected to obtain a nano-toughening agent;
[0055] (2) 30 g of lignin, 40 g of glycerol, 160 g of polyethylene glycol, and 12 g of lactic acid were mixed and added to a three-necked flask, a magnetic rotor was added to the three-necked flask, the three-necked flask was placed in an oil bath, a condenser was connected, and the mixture was heated to 160° C. and kept warm for 1 h. After filtration, the lignin polyol product was obtained by rotary evaporation as component A; glutamic acid was used as component B;
[0056] Component A and component B are mixed in a molar ratio of 1:1, added to a three-necked flask, and a nano toughener of 1‰ of the sum of the mass of component A and component B is added, and then a magnetic rotor is added, and the device is placed in an oil bath pot, and the condenser and the horn tube are connected, and the device is heated to 160°C, and the temperature is kept for reaction for 7 hours, and the device is cooled to room temperature, and the reaction product is taken out and dehydrated by rotary evaporation to obtain lignin-based polyester polyol;
[0057] (3) 4.9 g of bis(4-aminophenyl) diselenide and 3 g of 2-benzyl isocyanate were mixed and placed in a reactor, stirred continuously at 25° C. for 1 h, then placed in an ultrasonic oscillator for continuous oscillation for 30 min, and placed in a vacuum drying oven at 65° C. for drying overnight to remove bubbles, thereby obtaining a self-healing adhesive;
[0058] (4) Take 0.5 g of the self-healing adhesive synthesized in step (3), 0.165 g of the accelerator and 5 g of the lignin-based polyester polyol prepared in step (2), and stir them continuously for 15 min under a nitrogen atmosphere. Then, place them in an ultrasonic oscillator and stir them at 25 ° C for 5 min to remove bubbles. Then, continue to stir under a nitrogen atmosphere until the mixed solution shows signs of whitening, and let it stand for 3 hours to obtain a self-healing modified lignin-based polyester polyol coating material.
[0059] Example 2: Preparation of self-repairing modified lignin-based polyester polyol coating material
[0060] (1) 3 ml of concentrated sulfuric acid and 30 ml of tetrabutyl titanate were added to a 50 ml glass centrifuge tube, and then 0.5 g of nano-silica was added to the glass centrifuge tube, and the mixture was placed under continuous ultrasonic vibration for 2 hours to obtain a mixture; the mixture was then centrifuged in a high-speed centrifuge for 5 minutes (10,000 rpm), and the nano-silica loaded with tetrabutyl titanate and concentrated sulfuric acid was collected after removing the supernatant, and dried in a vacuum drying oven overnight and collected to obtain a nano-toughening agent;
[0061] (2) 30 g of lignin, 40 g of glycerol, 160 g of polyethylene glycol, and 12 g of lactic acid were mixed and added to a three-necked flask, a magnetic rotor was added to the three-necked flask, the three-necked flask was placed in an oil bath, a condenser was connected, and the mixture was heated to 160° C. and kept warm for 1 h. After filtration, the lignin polyol product was obtained by rotary evaporation as component A; cystine was used as component B;
[0062] Mix component A and component B in a molar ratio of 1:1, add them into a three-necked flask, add a nano-toughening agent of 1‰ of the sum of the masses of component A and component B, and then add a magnetic rotor. Place the device in an oil bath, connect the condenser and the ox-horn tube, heat the device to 195°C, keep the reaction warm for 8.5 hours, cool the device to room temperature, take out the reaction product and perform rotary evaporation to remove water to obtain lignin-based polyester polyol.
[0063] (3) 5 g of di-(1-hydroxyethyl) ditelluride and 3 g of 2-methoxyphenyl isocyanate were mixed and placed in a reactor, and stirred continuously at 25° C. for 1.5 h, and then placed in an ultrasonic oscillator for continuous oscillation for 30 min, and placed in a vacuum drying oven at 65° C. to dry overnight to remove some bubbles, thereby obtaining a self-healing adhesive;
[0064] (4) Take 0.5 g of the self-healing adhesive synthesized in step (3), 0.165 g of the accelerator and 5 g of the lignin-based polyester polyol prepared in step (2), and stir them continuously for 15 min under a nitrogen atmosphere. Then, place them in an ultrasonic oscillator and stir them at 25 ° C for 5 min to remove bubbles. Then, continue to stir under a nitrogen atmosphere until the mixed solution shows signs of whitening, and let it stand for 3 hours to obtain a self-healing modified lignin-based polyester polyol coating material.
[0065] Example 3: Preparation of self-repairing modified lignin-based polyester polyol coating material
[0066] (1) 3 ml of concentrated sulfuric acid and 30 ml of tetrabutyl titanate were added to a 50 ml glass centrifuge tube, and then 0.5 g of nano-silica was added to the glass centrifuge tube, and the mixture was placed under continuous ultrasonic vibration for 2 hours to obtain a mixture; the mixture was then centrifuged in a high-speed centrifuge for 5 minutes (10,000 rpm), and the nano-silica loaded with tetrabutyl titanate and concentrated sulfuric acid was collected after removing the supernatant, and dried in a vacuum drying oven overnight and collected to obtain a nano-toughening agent;
[0067] 2) 30 g of lignin, 40 g of glycerol, 160 g of polyethylene glycol and 12 g of lactic acid are mixed and added to a three-necked flask, a magnetic rotor is added to the three-necked flask, the three-necked flask is placed in an oil bath, a condenser is connected, the mixture is heated to 160° C., the mixture is kept warm for 1 h, and the lignin polyol product is obtained by rotary evaporation after filtration as component A; aspartic acid is used as component B.
[0068] Component A and component B are mixed in a molar ratio of 1:1, added to a three-necked flask, and a nano-toughening agent of 1‰ of the sum of the masses of component A and component B is added. Then a magnetic rotor is added, and the device is placed in an oil bath pot. The condenser and the ox-horn tube are connected, and the device is heated to 230°C and kept warm for 10 hours. The device is cooled to room temperature, and the reaction product is taken out for rotary evaporation to remove water to obtain lignin-based polyester polyol.
[0069] (3) 5 g of adenosine-2', 3'-o-phenyl borate and 2.5 g of 4-methoxyphenylethyl isocyanate were mixed and placed in a reactor, and stirred continuously at 25° C. for 1 h. The mixture was then placed in an ultrasonic oscillator and continuously shaken for 30 min. The mixture was placed in a vacuum drying oven at 65° C. and dried overnight to remove some bubbles, thereby obtaining a self-healing adhesive.
[0070] (4) Take 0.5 g of the self-healing adhesive synthesized in step (3), 0.165 g of the accelerator and 5 g of the lignin-based polyester polyol prepared in step (2), and stir them continuously for 15 min under a nitrogen atmosphere. Then, place them in an ultrasonic oscillator and stir them at 25 ° C for 5 min to remove bubbles. Then, continue to stir under a nitrogen atmosphere until the mixed solution shows signs of whitening, and let it stand for 3 hours to obtain a self-healing modified lignin-based polyester polyol coating material.
[0071] Example 4: Preparation of coated controlled-release fertilizer
[0072] Take 500g of polished urea granules and put them into a coating pan at 30°C. Keep the speed of the coating pan at 21rps. Use a spray gun to spray the self-repairing modified lignin-based polyester polyol coating material prepared in Example 1 onto the surface of the rolling urea granules. Curing for 15min, the spraying amount each time is 0.5% of the fertilizer mass. Repeat the above spraying operation until the weight of the sprayed coating liquid accounts for 4% of the total weight of the urea granules (ie, the coating thickness is 4%). After stabilization, the coated controlled-release fertilizer is obtained.
[0073] Example 5: Preparation of coated controlled-release fertilizer
[0074] Take 500g of polished urea granules and put them into a coating pan at 45°C. Keep the speed of the coating pan at 21rps. Use a spray gun to spray the self-repairing modified lignin-based polyester polyol coating material prepared in Example 2 onto the surface of the rolling urea granules. Curing for 10min, the spraying amount each time is 0.5% of the fertilizer mass. Repeat the above spraying operation until the weight of the sprayed coating liquid accounts for 4% of the total weight of the urea granules (ie, the coating thickness is 4%). After stabilization, the coated controlled-release fertilizer is obtained.
[0075] Example 6: Preparation of coated controlled-release fertilizer
[0076] Take 500g of polished urea granules and put them into a coating pan at 45°C. Keep the speed of the coating pan at 21rps. Use a spray gun to spray the self-repairing modified lignin-based polyester polyol coating material prepared in Example 3 onto the surface of the rolling urea granules. Curing for 13min, the spraying amount each time is 0.5% of the fertilizer mass. Repeat the above spraying operation until the weight of the sprayed coating liquid accounts for 5% of the total weight of the urea granules (ie, the coating thickness is 5%). After stabilization, the coated controlled-release fertilizer is obtained.
[0077] Comparative Example 1:
[0078] (1) 30 g of lignin, 40 g of glycerol, 160 g of polyethylene glycol, and 12 g of lactic acid were mixed and added to a three-necked flask, a magnetic rotor was added to the three-necked flask, the three-necked flask was placed in an oil bath, a condenser was connected, and the mixture was heated to 160° C. and kept warm for 1 h. After filtration, lignin polyol was obtained by rotary evaporation;
[0079] (2) 5 g of adenosine-2', 3'-o-phenyl borate and 2.5 g of 4-methoxyphenylethyl isocyanate were mixed and placed in a reactor, stirred continuously at 25° C. for 1 h, then placed in an ultrasonic oscillator for continuous oscillation for 30 min, and placed in a vacuum drying oven at 65° C. to dry overnight to remove some bubbles, thereby obtaining a self-healing adhesive;
[0080] (3) Take 0.5 g of the self-healing adhesive synthesized in step (2), 0.165 g of the accelerator and 5 g of the lignin polyol prepared in step (1), stir continuously for 15 min under a nitrogen atmosphere, then place in an ultrasonic oscillator and stir at 25 ° C for 5 min to remove bubbles, then continue to stir under a nitrogen atmosphere until the mixed solution shows signs of whitening, and let it stand for 3 hours to obtain a self-healing modified lignin-based polyester polyol coating material;
[0081] (4) Take 500 g of polished urea granules and put them into a coating pan at 30°C. Keep the speed of the coating pan at 21 rps. Use a spray gun to spray the above self-repairing modified lignin-based polyester polyol coating material onto the surface of the rolling urea granules and cure for 15 minutes. The spraying amount each time is 0.5% of the fertilizer mass. Repeat the above spraying operation until the weight of the sprayed coating liquid accounts for 4% of the total weight of the urea granules (i.e., the coating thickness is 4%). After stabilization, the coated controlled-release fertilizer is obtained.
[0082] Compared with Example 6, this example uses lignin polyol to replace the lignin-based polyester polyol in the coating material.
[0083] Comparative Example 2:
[0084] (1) 30 g of lignin, 40 g of glycerol, 160 g of polyethylene glycol, and 12 g of lactic acid were mixed and added to a three-necked flask, a magnetic rotor was added to the three-necked flask, the three-necked flask was placed in an oil bath, a condenser was connected, and the mixture was heated to 160° C. and kept warm for 1 h. After filtration, the lignin polyol product was obtained by rotary evaporation as component A; aspartic acid was used as component B;
[0085] Component A and component B were mixed in a molar ratio of 1:1, added to a three-necked flask, and then a magnetic rotor was added. The device was placed in an oil bath, and the condenser and the ox-horn tube were connected. The device was heated to 160°C and kept warm for 7 hours. The device was cooled to room temperature, and the reaction product was taken out for rotary evaporation to remove water to obtain lignin-based polyester polyol.
[0086] (2) 5 g of adenosine-2', 3'-o-phenyl borate and 2.5 g of 4-methoxyphenylethyl isocyanate were mixed and placed in a reactor, stirred continuously at 25° C. for 1 h, then placed in an ultrasonic oscillator for continuous oscillation for 30 min, and placed in a vacuum drying oven at 65° C. for drying overnight to remove bubbles, thereby obtaining a self-healing adhesive;
[0087] (3) Take 0.5 g of the self-healing adhesive synthesized in step (3), 0.165 g of the accelerator and 5 g of the lignin-based polyester polyol prepared in step (2), and stir them continuously for 15 min under a nitrogen atmosphere, then place them in an ultrasonic oscillator and stir them at 25 ° C for 5 min to remove bubbles, then continue to stir under a nitrogen atmosphere until the mixed solution shows signs of whitening, and let it stand for 3 hours to obtain a self-healing modified lignin-based polyester polyol coating material;
[0088] (4) Take 500 g of polished urea granules and put them into a coating pan at 30°C. Keep the speed of the coating pan at 21 rps. Use a spray gun to spray the above self-repairing modified lignin-based polyester polyol coating material onto the surface of the rolling urea granules and cure for 15 minutes. The spraying amount each time is 0.5% of the fertilizer mass. Repeat the above spraying operation until the weight of the sprayed coating liquid accounts for 4% of the total weight of the urea granules (i.e., the coating thickness is 4%). After stabilization, the coated controlled-release fertilizer is obtained.
[0089] Compared with Example 6, the lignin-based polyester polyol in this example is prepared from lignin polyol and aspartic acid.
[0090] Comparative Example 3:
[0091] (1) 3 ml of concentrated sulfuric acid and 30 ml of tetrabutyl titanate were added to a 50 ml glass centrifuge tube, and then 0.5 g of nano-silica was added to the glass centrifuge tube, and the mixture was placed under continuous ultrasonic vibration for 2 hours to obtain a mixture; the mixture was then centrifuged in a high-speed centrifuge for 5 minutes (10,000 rpm), and the nano-silica loaded with tetrabutyl titanate and concentrated sulfuric acid was collected after removing the supernatant, and dried in a vacuum drying oven overnight and collected to obtain a nano-toughening agent;
[0092] (2) 30 g of lignin, 40 g of glycerol, 160 g of polyethylene glycol, and 12 g of lactic acid were mixed and added to a three-necked flask, a magnetic rotor was added to the three-necked flask, the three-necked flask was placed in an oil bath, a condenser was connected, and the mixture was heated to 160° C. and kept warm for 1 h. After filtration, lignin polyol was obtained by rotary evaporation;
[0093] Add lignin polyol to a three-necked flask, add a nano toughener with a mass of 1‰ of the lignin polyol, then add a magnetic rotor, place the device in an oil bath, connect the condenser and the ox-horn tube, heat the device to 160°C, keep the temperature for 7 hours, cool the device to room temperature, take out the reaction product, and perform rotary evaporation to remove water to obtain nano toughener-modified lignin polyol;
[0094] (3) 5 g of adenosine-2', 3'-o-phenyl borate and 2.5 g of 4-methoxyphenylethyl isocyanate were mixed and placed in a reactor, stirred continuously at 25° C. for 1 h, then placed in an ultrasonic oscillator for continuous oscillation for 30 min, and placed in a vacuum drying oven at 65° C. to dry overnight to remove bubbles, thereby obtaining a self-healing adhesive;
[0095] (4) Take 0.5 g of the self-healing adhesive synthesized in step (3), 0.165 g of the accelerator and 5 g of the nano-toughening agent-modified lignin polyol prepared in step (2), and stir them continuously for 15 min under a nitrogen atmosphere. Then, place them in an ultrasonic oscillator and stir them at 25 ° C for 5 min to remove bubbles. Then, continue to stir under a nitrogen atmosphere until the mixed solution shows signs of whitening, and let it stand for 3 hours to obtain a self-healing modified lignin-based polyester polyol coating material.
[0096] (4) Take 500 g of polished urea granules and put them into a coating pan at 30°C. Keep the speed of the coating pan at 21 rps. Use a spray gun to spray the above self-repairing modified lignin-based polyester polyol coating material onto the surface of the rolling urea granules and cure for 15 minutes. The spraying amount each time is 0.5% of the fertilizer mass. Repeat the above spraying operation until the weight of the sprayed coating liquid accounts for 4% of the total weight of the urea granules (i.e., the coating thickness is 4%). After stabilization, the coated controlled-release fertilizer is obtained.
[0097] Compared with Example 6, this example uses lignin polyol modified with a nano toughening agent to replace the lignin-based polyester polyol.
[0098] Test Example 1: Performance investigation of self-healing modified lignin-based polyester polyol coating materials
[0099] The self-repairing modified lignin-based polyester polyol coating material prepared in Example 1 was cured to form a membrane shell. The changes of characteristic groups in the membrane shell were detected by Fourier transform infrared spectroscopy. The results were as follows: Figure 2 As shown, two characteristic peaks of polyurethane, NH group and C=O group, appear, -NCO group disappears completely, and a polyurethane coating has been formed on the surface.
[0100] The surface and cross section of the polyurethane coating formed by the coating material of Example 1 were observed using a scanning electron microscope (SEM). Figure 3 As shown, the addition of nano toughening agent makes the surface and cross section of the coating smoother and denser.
[0101] Test Example 2: Investigation of the performance of the coated controlled-release fertilizer prepared using the coating material of the present invention
[0102] 1. Nutrient release determination:
[0103] The nitrogen release rate of the coated controlled-release fertilizer prepared in Example 4-6 was measured according to the National Standard for Slow-Release Fertilizers GB / T23348-2009.
[0104] The results are as follows Figure 4 As shown, the release period of the bio-based coated fertilizer in Example 4 is 45 days; the release period of the bio-based coated fertilizer in Example 5 is 50 days, and the release period of the bio-based coated controlled-release fertilizer in Example 6 is 54 days.
[0105] However, in Comparative Examples 1 and 2, no nano toughening agent was added, and a large area of the membrane shell was torn and damaged during the coating. Therefore, the membrane material could not completely coat the surface of the fertilizer particles, and its controlled release period was the same as that of ordinary urea. It could be completely dissolved in water in ten minutes, and its controlled release period could not be measured. In Comparative Example 3, no amino-containing dibasic acid was added, and the nano toughening agent and the lignin-based polyol could not react chemically, but only a simple physical blending was performed. Therefore, during the coating, the film was uneven, the membrane shell was torn in large pieces, and the fertilizer particles could not be completely coated, and there was no controlled release effect. Therefore, only when the three exist at the same time and the coating liquid obtained after the reaction can the fertilizer particles be completely coated.
[0106] 2. Investigation of self-repair performance under visible light
[0107] The coating material prepared in Example 1 was cut into two pieces with scissors, and then the two pieces of coating material were put together. After 2 hours at room temperature and under visible light, the healing of the scratch was observed.
[0108] like Figure 5 As shown, under visible light, the two broken pieces of the coating material of the present application can be re-bonded together, and the repair effect is good.
[0109] Figure 6 The toughness comparison is between the coating material with the nano toughening agent added in Example 1 and the coating material without the nano toughening agent in Comparative Example 2. The film material without the nano toughening agent cannot be completely coated on the surface of the fertilizer particles.
[0110] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A self-repairing modified lignin-based polyester polyol coating material, characterized in that: The invention comprises the following raw materials in parts by weight: 50-100 parts of lignin-based polyester polyol, 0-2 parts of accelerator and 1-20 parts of self-healing adhesive; The self-healing adhesive is obtained by reacting a first component and a second component, wherein the first component is one or more of adenosine-2', 3'-o-phenyl borate, bis(4-aminophenyl) diselenide, and di-(1-hydroxyethyl) ditelluride; and the second component is one or more of 2-benzyl isocyanate, 2-methoxyphenyl isocyanate, and 4-methoxyphenylethyl isocyanate; The self-healing adhesive is prepared by the following method: The first component and the second component are mixed in a mass ratio of (4-6): (2-4), reacted at 20-30° C. for 1-2 hours, dried at 65° C. for 10-14 hours, and bubbles are removed to obtain a self-healing adhesive; The lignin-based polyester polyol is prepared by the following method: The lignin polyol and the amino-containing dicarboxylic acid are mixed in a molar ratio of 1:1 to obtain a mixed solution, and then a nano toughener of 1‰ of the mixed solution mass is added to the mixed solution, and the mixture is reacted at 160°C-230°C for 6-10h, and the product is dehydrated after the reaction to obtain a lignin-based polyester polyol; The nano toughening agent is prepared by the following method: Concentrated sulfuric acid and tetrabutyl titanate are mixed to obtain a mixed solution, and then nano-silicon dioxide is added to the mixed solution, vibrated for 2 hours, and the precipitate is collected by centrifugation and dried to obtain a nano-toughening agent; The ratio of the added amounts of concentrated sulfuric acid, tetrabutyl titanate and nano-silicon dioxide is (2-4) ml: (25-35) ml: (0.1-1) g; The accelerator is 5-aminolevulinic acid hydrochloride.
2. A self-repairing modified lignin-based polyester polyol coating material according to claim 1, characterized in that: The invention comprises the following raw materials in parts by weight: 50-100 parts of lignin-based polyester polyol, 1.5-2 parts of accelerator and 1-20 parts of self-healing adhesive.
3. A self-repairing modified lignin-based polyester polyol coating material according to claim 1, characterized in that: The amino-containing dicarboxylic acid is one or more of glutamic acid, cysteine and aspartic acid.
4. The method for preparing the self-repairing modified lignin-based polyester polyol coating material according to any one of claims 1 to 3, characterized in that: The following steps are involved: The lignin-based polyester polyol, the accelerator and the self-healing adhesive are mixed evenly, stirred continuously for 10-20 minutes under a nitrogen atmosphere, bubbles are removed, and the mixture is allowed to stand for 2-4 hours to obtain a self-healing modified lignin-based polyester polyol coating material.
5. Use of the self-repairing modified lignin-based polyester polyol coating material according to any one of claims 1 to 3 in the preparation of controlled-release fertilizers.
6. A coated controlled-release fertilizer, characterized in that: It comprises a fertilizer core, and the self-repairing modified lignin-based polyester polyol coating material according to any one of claims 1 to 3 sprayed on the surface of the fertilizer core; the mass of the self-repairing modified lignin-based polyester polyol coating material is 4-6% of the mass of the fertilizer core.
7. The method for preparing the coated controlled-release fertilizer according to claim 6, characterized in that: The following steps are involved: The self-repairing modified lignin-based polyester polyol coating material according to any one of claims 1 to 3 is uniformly sprayed on the surface of the fertilizer core at a rotation speed of 20-23 rps at a pressure of 0.2-0.5 MPa, and cured at 50-70° C. for 10-15 minutes to obtain a coated controlled-release fertilizer.
Citation Information
Patent Citations
Bio-based polymer coating material, coated controlled-release fertilizer and preparation method of coated controlled-release fertilizer
CN113105604A
Bio-based membrane with self-repairing function, coated controlled-release fertilizer and preparation method
CN113788711A